Answer:
The roots of the equation, 3.1·x³ - 2.4·x²+ 6·x - 3 = 4·x² + 3·x + 2, are;
x = 1.986, x = 0.0392 - 0.9·i, x = 0.0392 + 0.9·i
Explanation:
The given equation is 3.1·x³ - 2.4·x²+ 6·x - 3 = 4·x² + 3·x + 2
Which gives;
3.1·x³ - 2.4·x²+ 6·x - 3 - 4·x² - 3·x - 2 = 0
3.1·x³ - 6.4·x²+ 3·x - 5 = 0
Factorizing online, we get;
3.1·x³ - 6.4·x²+ 6·x + 3·x - 5 = 3.1·(x - 1.986)·(x² - 0.0784·x + 0.812) = 0
Therefore, the possible solutions are;
x - 1.986= 0 or x² - 0.0784·x + 0.812 = 0
The roots of the equation are x² - 0.0784·x + 0.812 = 0 are;
x = 0.0392 - 0.9·i, x = 0.0392 + 0.9·i
Therefore, the roots of the equation, 3.1·x³ - 2.4·x²+ 6·x - 3 = 4·x² + 3·x + 2, are;
x = 1.986, x = 0.0392 - 0.9·i, x = 0.0392 + 0.9·i.